Greening animal farm: A case study for a pig farm / Ananda Pragasha Nair - Ananda , Pragasha Nair (2021)
Pork meat is a highly consumed globally due to good taste and being relatively more nutritious than red meat. Hence, there is always a growing demand and need for intensive pig farm production. Currently, successfully operated pig farms practise closed-farming system, also termed Modern Pig Farm (MPF), which basically means all farming operations are done indoors, including waste storage and treatment. The Penang Government had recently passed a law mandating all Penang pig farms to meet the requirements of a MPF system. A pig farm in Penang (open-air farm) was identified as case study for this Research, with the main aim of providing sustainable green farming measures to improve the farm’s overall performance to meet MPF standard. A site visit was held at the farm for site observation and data collection. The sample for raw pig waste was also collected at the farm and sent for laboratory analysis. The total pig waste generation was estimated at 51 tonnes/day. A conceptual design for the farm’s overall waste treatment system was able to be provided, using a combination of different components for an overall Biogas system integration that will not allow discharge of solid or liquid if it does not meet the relevant discharge regulation parameter. There were many ore recommendations for greening measures described in this Study, covering all aspects of farming production, such as improving pig pen design for better wastewater collection and reducing food waste, odour control methods, disinfection protocols, diet manipulation of pigs for higher growth performance, lesser chance of disease transmission, drainage design for optimum waste flow and others. This shows that there are many potential greening tools and measures for further improvement on sustainable pig farming.